2004
DOI: 10.1248/bpb.27.1775
|View full text |Cite
|
Sign up to set email alerts
|

Licorice Flavonoids Suppress Abdominal Fat Accumulation and Increase in Blood Glucose Level in Obese Diabetic KK-Ay Mice

Abstract: Licorice, the root of the leguminous Glycyrrhiza plant species, has been used for over 4000 years since ancient Egyptian times, and is one of the most frequently employed botanicals in traditional medicines.1) There are several species of licorice, including Glycyrrhiza uralensis FISCHER, G. glabra LINNE and G. inflata BATALIN, and they include species-specific flavonoids.1,2) Our previous study showed that nonaqueous fractions of G. uralensis have peroxisome proliferator-activated receptor-g (PPAR-g) ligand-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 37 publications
2
74
0
3
Order By: Relevance
“…7,8) There are several species of licorice, including Glycyrrhiza uralensis FISCHER, G. glabra LINNE, and G. inflate BATALIN, and each of which contains speciesspecific flavonoids. 9,10) Licorice flavonoid oil (LFO), which contains hydrophobic flavonoids from G. glabra LINNE, is a new ingredient for functional foods. [9][10][11][12] We recently found that LFO decreases the size of hepatic lipid droplets, which are mainly composed of triglyceride (TG), and abdominal adipose tissue weight in diet-induced obese mice.…”
Section: Investigation Of the Anti-obesity Action Of Licorice Flavonomentioning
confidence: 99%
“…7,8) There are several species of licorice, including Glycyrrhiza uralensis FISCHER, G. glabra LINNE, and G. inflate BATALIN, and each of which contains speciesspecific flavonoids. 9,10) Licorice flavonoid oil (LFO), which contains hydrophobic flavonoids from G. glabra LINNE, is a new ingredient for functional foods. [9][10][11][12] We recently found that LFO decreases the size of hepatic lipid droplets, which are mainly composed of triglyceride (TG), and abdominal adipose tissue weight in diet-induced obese mice.…”
Section: Investigation Of the Anti-obesity Action Of Licorice Flavonomentioning
confidence: 99%
“…More recently, Wolfram et al (2005) showed that supplementation with Teavigo ® , a green tea extract containing about 94% EGCG, abolishes diet-induced obesity and claimed that this was a valuable natural treatment option for obesity. Nakagawa et al (2004) demonstrated the abdominal fat lowering and hypoglycemic effects of licorice hydrophobic flavonoids in obese diabetic mice and elucidated their mechanisms of action by showing that they induce differentiation of human adipocytes. Sugiyama et al (2007) suggested that oligomeric procyanidin was the main contributor to the effect of apple polyphenol extract on inhibiting triglyceride absorption in mice and humans.…”
Section: Chardonnay Grape Seed Procyanidin Extractmentioning
confidence: 99%
“…Our previous study suggested that LFO is effective in reducing visceral fat accumulation and suppressing elevated blood glucose levels in obese diabetic KK-Ay mice (2). Subsequently, a double-blind placebo-controlled clinical trial showed that LFO was effective in suppressing body weight gain by reducing body fat mass in overweight volunteers (3).…”
mentioning
confidence: 99%
“…Licorice flavonoid oil (LFO) is a new functional food ingredient containing hydrophobic flavonoids derived from G. glabra (2). Our previous study suggested that LFO is effective in reducing visceral fat accumulation and suppressing elevated blood glucose levels in obese diabetic KK-Ay mice (2).…”
mentioning
confidence: 99%